2018
DOI: 10.1007/s40261-018-0702-9
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Elbasvir/Grazoprevir Versus Daclatasvir Plus Asunaprevir in Patients with Chronic Hepatitis C Virus Genotype 1b Infection in China

Abstract: Treatment with EBR/GZR was the cost-effective option for patients with chronic HCV GT1b infection in China, regardless of cirrhosis status or treatment history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…29 Another study indicated that EBR/GZR was more cost-effectiveness than DCV/ASV. 36 In addition, Wu et al evaluated cost-effectiveness of DAAs including DCV/ASV, 3D, SR and SD, which showed 3D was the most effective in Chinese patients with GT1b. 32 There are several cost-effectiveness studies in other countries comparing the SOF/VEL with other all-oral DAA treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Another study indicated that EBR/GZR was more cost-effectiveness than DCV/ASV. 36 In addition, Wu et al evaluated cost-effectiveness of DAAs including DCV/ASV, 3D, SR and SD, which showed 3D was the most effective in Chinese patients with GT1b. 32 There are several cost-effectiveness studies in other countries comparing the SOF/VEL with other all-oral DAA treatments.…”
Section: Discussionmentioning
confidence: 99%
“… 29 Another study indicated that EBR/GZR was more cost-effectiveness than DCV/ASV. 36 In addition, Wu et al evaluated cost-effectiveness of DAAs including DCV/ASV, 3D, SR and SD, which showed 3D was the most effective in Chinese patients with GT1b. 32 …”
Section: Discussionmentioning
confidence: 99%
“…The efficiency and costs of these regimens were similar to DCV + ASV [33]. Previous studies have proven that DAAs were highly cost-effective compared with PR [34,35], however, as DAAs were not included in the national health insurance drug lists, patients had to pay out of their own pockets [36].…”
Section: Discussionmentioning
confidence: 99%
“…One of the aforementioned studies simulating 10000 Chinese CHC patients with various HCV genotypes predicted that all the then-available second-generation DAA regimens (DCV + ASV, O/P/r + D, SOF/VEL, and EBR/GZR) would have cost-effectiveness advantages over PR therapy, with the pan-genotypic SOF/VEL conferring the greatest gain in QALYs (by 17%) and reduction in lifetime cost (by 49%) relative to PR[56]. Among genotype-specific DAA regimens, one study predicted that for GT1b Chinese patients stratified by cirrhosis status and treatment history, EBR/GZR would be more cost-effective than DCV + ASV[99].…”
Section: Economic and Societal Value Of Curing Hcv Infectionmentioning
confidence: 99%